INCREASE OF WEARPROOF OF BAND-BLOCK BRAKES OF DRILLING HOISTS BY THE SERVE OF EXHAUST GASES TO INTERCONTACT SPACE OF FRICTION SURFACES - Криштопа, Святослав Ігорович; Криштопа, Людмила Іванівна; Пітулей, Лоліта Дмитрівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Destruction of connective asbopolymer materials at intercontact space has a difficult character depending on the modes of friction and mechanical, physical and chemical properties of friction surface can get the positive or negative value. Surplus pressure hinders to migration in between contact space of environment and creates terms for formation areas of pellicle starvation. According to laboratory and natural researches gas dynamic effects taking place in intercontact space of friction pairs and hard loading friction units of band-block brakes of drilling hoists work at surplus pressure is created in intercontact space. The analysis of results of researches showed the necessity of the forced input of gas environment for intercontact space with surplus pressure which must exceed pressure of gaseous products of destruction of connective asbopolymer materials. The system and method of serve of gas environment is developed, for example, exhaust gases of combustion engines on the friction contact with the purpose of increase of liveability of the brake. Article is devote to the problem of necessity of the forced inputing of gas environment for intercontact space of hard loading friction units of band-block brakes of drilling hoists with surplus pressure which must exceed pressure of gaseous products of destruction of connective asbopolymer materials. System and method of serve of gas environment is developed, for example, exhaust gases of combustion engines on the friction contact with the purpose of increase of liveability of the brake.